2023
DOI: 10.9734/ijecc/2023/v13i31699
|View full text |Cite
|
Sign up to set email alerts
|

Stage Specific Life Table of Rice Leaffolder, Cnaphalocrocis medinalis (Guen.) at Different Temperature Regimes

Abstract: The change in air temperature will influence the insect behavior, physiology and population dynamics of insects as they are poikilothermic. Global temperature has increased by 1.09°C during 2001-2020 when compared to 1850-1900. It is projected that the temperature will further increase by 5.7°C under high emission scenario, if mitigation strategies are not adopted. Increase in temperature would affect the physiology and population dynamics of the insects. A study was undertaken to understand the effect of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Earlier a high rate of egg mortality had been reported as a common trait (Cuthbertson et al, 2013) and among Lepidopteran insects' mortality during the early larval stages is typically significant (Soufbaf et al, 2010). Similar to the present study, Park et al (2014) reported high egg mortality (43%); and Jian et al (2012) and Manikandan et al (2023) reported high early larval mortality and pupal survival while rearing C. medinalis at 27± 1°C on rice leaves. The results observed by Ankit et al (2016) are also in line with the present study in terms of egg hatching (63.45%), while higher pupation (56.66%) was reported, which might be due to the varietal difference or variation in the temperature and humidity conditions of rearing.…”
Section: Resultssupporting
confidence: 87%
“…Earlier a high rate of egg mortality had been reported as a common trait (Cuthbertson et al, 2013) and among Lepidopteran insects' mortality during the early larval stages is typically significant (Soufbaf et al, 2010). Similar to the present study, Park et al (2014) reported high egg mortality (43%); and Jian et al (2012) and Manikandan et al (2023) reported high early larval mortality and pupal survival while rearing C. medinalis at 27± 1°C on rice leaves. The results observed by Ankit et al (2016) are also in line with the present study in terms of egg hatching (63.45%), while higher pupation (56.66%) was reported, which might be due to the varietal difference or variation in the temperature and humidity conditions of rearing.…”
Section: Resultssupporting
confidence: 87%